A High-Reliability Organization Framework for Health Care: A Multiyear Implementation Strategy and Associated Outcomes. Issue 1 (January 2022) - Sculli, Gary L.; Pendley-Louis, Robin; Neily, Julia; Anderson, Timothy M.; Isaacks, David B.; Knowles, Regina; Young-Xu, Yinong; Gunnar, William
Abstract : Objectives: Applying high-reliability organization (HRO) principles to health care is complex. No consensus exists as to an effective framework for HRO implementation or the direct impact of adoption. Methods: The Veterans Health Administration (VHA) National Center for Patient Safety established the high-reliability hospital (HRH) model for HRO adoption and piloted HRH in collaboration with the Truman VA Medical Center (Truman) during a 3-year intervention period (January 1, 2016–December 31, 2018). High-reliability hospital components are as follows: annual patient safety (PS) assessment, annual PS culture survey, annual root cause analysis training, daily leadership walk-arounds, monthly PS forum, annual processes standardization review, Just Culture training, unit-based Clinical Team Training, unit-based continuous improvement projects, and annual Clinical Team Training simulation education. The impact of HRH was examined using a PS Culture Survey, PS event reporting, and quality outcomes of standardized mortality rate and complication rate. Results: Truman internally improved PS culture and PS event reporting rates resulting in outcomes better than all VHA facilities (All VHA; P < 0.001 and P < 0.001, respectively). Low-harm PS event reporting increased ( P < 0.001); however, serious safety event rate remained unchanged versus All VHA. Significant improvement in Truman standardized mortality rate and complication rate versus All VHA occurred immediately and were sustained through intervention (slopes, P < 0.001 and P < 0.020; respectively). Conclusions: High-reliability hospital is an effective framework for HRO implementation and will be applied to 18 additional VHA sites. Based on these results, the expected outcome will be improved PS culture and overall PS event reporting. The impact of HRH on serious safety event rate and quality measures requires further study.